Effect of Administrative Governance on Job Performance: A Field Study on Health Centers Employees in Alqurayyat Governorate - Alanazi, Hmood Alhadi Nafea; Alshammari, Wael Shafi Manzil (The Arab Journal of Administration, 2025)
This study aimed at recognizing the effect of administrative governance, with its principles: (justice, transparency, accountability, integrity, participation, and administrative empowerment) on job performance at health centers in Alqurayyat Governorate. The study adopted the analytical descriptive approach. A questionnaire was used as a main tool for obtaining the required data from the random study sample that comprised (152) employees at health centers in Alqurayyat Governorate, where most of them were males (61.8%), with females representing (32.8%) of the sample. The study concluded many important findings that may help in supporting the orientation towards governance of health centers specifically, and all health organizations and utilities at the whole kingdom level in general. It revealed that applying the principles of governance is at a moderate level, appropriate for job performance, and it also indicated the existence of statistically significant differences in principles of administrative governance according to the gender, and educational qualification variables. The study recommended attempting to enhance the principles of administrative governance with its several aspects, not concentrating on certain aspects, highlighting its findings in health sectors to be more aware of the concept of health quality management with its standards and dimensions, and enhancing the role of employees at health sectors and centers for the level of activating health organizations governance role in order to reinforce the application of quality principles at these centers. The study recommended attempting to enhance the principles of governance from its several aspects and not focusing on certain aspects, in addition to highlighting its results in health sectors to be more aware according to the concept of health quality, its aspects, and its standards. Furthermore, the study recommended enhancing the role of health sectors and centers to the level of activating the role of governance of health institutions, in order to reinforce applying the principles of quality in these centers. The researcher also introduced many research suggestions, the most prominent of which were: conducting a study that is similar to the current one as an applied study comprising all other governmental sectors and organizations, and conducting further future studies on the obstacles that hamper the adherence of health organizations to principles of governance.